Constructing the Prussia-Myth in East Germany, 1945–61. (July 2019) - Colla, Marcus
In postwar East Germany, dealing with the history of Prussia was problematic. While 'Prussianism' or the 'Spirit of Prussia' was widely perceived as a central cause of Nazism, it also could not be ignored when developing 'progressive' narratives of German history. This article investigates the political, intellectual and symbolic construction of a 'Prussia-myth' in the early postwar years. In particular, it investigates how the 'Prussia-myth' was adapted to changing political conditions, the theoretical contradictions this engendered, and the manner in which historians and cultural figures dealt with these problems when educating the East German population at large.